Placental Abnormalities and Placenta-Related Complications Following In-Vitro Fertilization: Based on National Hospitalized Data in China - Kong, Fei; Fu, Yu; Shi, Huifeng; Li, Rong; Zhao, Yangyu; Wang, Yuanyuan; Qiao, Jie (Frontiers in Endocrinology, 2022)
Introduction Emerging evidence has shown that in-vitro fertilization (IVF) is associated with higher risks of certain placental abnormalities or complications, such as placental abruption, preeclampsia, and preterm birth. However, there is a lack of large population-based analysis focusing on placental abnormalities or complications following IVF treatment. This study aimed to estimate the absolute risk of placental abnormalities or complications during IVF-conceived pregnancy. Methods We conducted a retrospective cohort study of 16 535 852 singleton pregnancies with delivery outcomes in China between 2013 and 2018, based on the Hospital Quality Monitoring System databases. Main outcomes included placental abnormalities (placenta previa, placental abruption, placenta accrete, and abnormal morphology of placenta) and placenta-related complications (gestational hypertension, preeclampsia, eclampsia, preterm birth, fetal distress, and fetal growth restriction (FGR)). Poisson regression modeling with restricted cubic splines of exact maternal age was used to estimate the absolute risk in both the IVF and non-IVF groups. Results The IVF group (n = 183 059) was more likely than the non-IVF group (n = 16 352 793) to present placenta previa (aRR: 1.87 [1.83–1.91]), placental abruption (aRR: 1.16 [1.11–1.21]), placenta accrete (aRR: 2.00 [1.96–2.04]), abnormal morphology of placenta (aRR: 2.12 [2.07 to 2.16]), gestational hypertension (aRR: 1.55 [1.51–1.59]), preeclampsia (aRR: 1.54 [1.51–1.57]), preterm birth (aRR: 1.48 [1.46–1.51]), fetal distress (aRR: 1.39 [1.37–1.42]), and FGR (aRR: 1.36 [1.30–1.42]), but no significant difference in eclampsia (aRR: 0.91 [0.80–1.04]) was found. The absolute risk of each outcome with increasing maternal age in both the IVF and non-IVF group presented two patterns: an upward curve showing in placenta previa, placenta accreta, abnormal morphology of placenta, and gestational hypertension; and a J-shape curve showing in placental abruption, preeclampsia, eclampsia, preterm birth, fetal distress, and FGR. Conclusion IVF is an independent risk factor for placental abnormalities and placental-related complications, and the risk is associated with maternal age. Further research is needed to evaluate the long-term placenta-related chronic diseases of IVF patients and their offspring.